Angiogenesis in the pathogenesis of inflammatory joint and lung diseases - Walsh, D.A.; Pearson, C.I. (BioMEd Central, 2001)
This paper reviews hypotheses about roles of angiogenesis in the pathogenesis of inflammatory disease in two organs, the synovial joint and the lung. Neovascularisation is a fundamental process for growth and tissue repair after injury. Nevertheless, it may contribute to a variety of chronic inflammatory diseases, including rheumatoid arthritis, osteoarthritis, asthma, and pulmonary fibrosis. Inflammation can promote angiogenesis, and new vessels may enhance tissue inflammation. Angiogenesis in inflammatory disease may also contribute to tissue growth, disordered tissue perfusion, abnormal ossification, and enhanced responses to normal or pathological stimuli. Angiogenesis inhibitors may reduce inflammation and may also help to restore appropriate tissue structure and function